Outcome of Early-Stage Glottic Laryngeal Carcinoma Patients Treated with Radical Radiotherapy Using Different Techniques - Cetinayak, Oguz (J Oncol, 2019)
PURPOSE: The aim was to evaluate the treatment outcomes and prognostic characteristics of patients with early-stage glottic laryngeal carcinoma who underwent radical radiotherapy (RT) with different techniques. PATIENTS AND METHODS: Radiotherapy was applied using the 2D conventional technique between 1991 and 2004 (130 patients), 3DCRT until 2014 (125 patients), and by VMAT until January 2017 (44 patients). Clinical T stages were 38 (12.7%) for Tis, 209 (69.9%) for T1, and 52 (17.4%) for T2. Radiotherapy technique and energy, anterior commissure involvement, and stage were analyzed as prognostic factors. RESULTS: The median total dose was 66 (50–70) Gy, and median follow-up time was 72 (3–288) months; 5-year disease-specific survival (DSS) rates were 95.8%, 95.5%, and 88.6%, respectively, in Tis, T1, and T2 stages. In multivariate analyses, anterior commissure involvement was found significant for all survival and local control rates. The patients treated with VMAT technique had better local control and DSS rates. However, these results were not statistically significant. CONCLUSION: In early-stage laryngeal carcinomas, radical RT is a function sparing and effective treatment modality, regardless of treatment techniques.